(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
Municipal solid waste landfills are one of the most dangerous environment “point" polluters. The main polluter in landfills is leachate, which arise mainly of waste moisture and precipitations. Leachate is very contaminated wastewater and all landfills operators have problems in leachate treatment sector, because composition of leachate contaminants and concentrations very changed in time. It is very problematic task for selection of leachate treatment method or methods. Normally, in leachate treatment practice combination of different treatment methods are used. In this paper composition of leachate in two biggest Latvia landfills are described. Leachate treatment investigations were achieved with coagulation and sorbtion methods. In researches leachate with coagulants Al2(SOf3 and FeCl3 and peat as sorbent are treated. Researches showed that peat is very effective sorbent for heavy metals removing from leachate.